The impact of EU structural fund support and problems of its absorption - Jurevičienė, Daiva; Pileckaitė, Jūratė (Business, Management and Economics Engineering, 2013)
Targeted allocation of EU support in Lithuania can help resolving a number of problems and achieving significant results in a variety of areas. However, rush to absorb support may lead to a little, zero or even negative impact on national economy. In addition, EU support opportunities may distort investment motivation. This paper deals with issues related to the impact of EU support and problems of its absorption. The impact of EU support on the national economy has been established in three areas: attraction of foreign direct investment state investments into capital formation, and experience of companies, which are EU support beneficiaries. The paper proposes using regression analysis in search and evaluation of relations while obtaining more information about programmes, priorities and the impact of structural support on different indicators. In addition, it focuses on ascertaining the effectiveness of governmental and company spending. Furthermore, as companies – EU support beneficiaries – are engaged in different economic activities, their experience cannot be ascertained from statistical data; consequently, findings of an expert survey are presented to demonstrate the experience acquired by business companies as well as problems they face. Limitation of research was a short period of time to evaluate (only four years of the current funding period)